A new sublime ten timeless lessons on the classics - Boitani, Piero 1947- (Europa Editions, 2020)
The classics "never exhaust what they have to say". Informed by this belief, linguistic expert Piero Boitani invites the reader to explore the wisdom of the works of literature underpinning Western culture, and highlights their profound and sometimes surprising connection to the present. The themes explored in this book are as wide-ranging as they are enduringly relevant. They include the Iliad's depiction of power and war, as well as its invocation of compassion as one of the necessary foundations of society; the Odyssey as the world's first novel; Lucretius and the way he transformed Greek scientific thought into sublime poetry; Virgil's celebration of the history of Rome, from small village to world capital, as well as Tacitus' denunciation of the imperialistic nature of Roman power; and Ovid's Metamorphoses--a poem about incessant change the first postmodern classic
Translation of: Dieci lezioni sui classici
Original title: Dieci lezioni sui classici; Bologna : Società editrice il Mulino, ©2017
"Europa Compass"--Front cover
Keywords: Literatur; Latein; Griechisch; Classical literature / History and criticism; Classical literature; Criticism, interpretation, etc